EFL Instruction Methods And Techniques With An Islamic Perspective - Fiveronika; Amalia Putri; Elsa Mulia Adha; Ilma Hidayah; Hasnah Luthfiyah; Khalayo Hasibuan (English Lecturers and Teachers Association (ELTA), 2026)
This study explores the integration of Islamic perspectives into English as a Foreign Language (EFL) instruction and its potential to enhance both linguistic competence and moral development among Muslim learners. Many conventional EFL teaching methods are rooted in Western pedagogical paradigms, which often overlook the cultural and spiritual values of students in Islamic educational contexts. This study aims to examine how Islamic values can be systematically incorporated into EFL instructional methods while maintaining their effectiveness in language acquisition.The study employs a qualitative research design using a systematic literature review. Relevant academic sources were collected from databases such as Google Scholar, ERIC, and ResearchGate. The data were analyzed using thematic analysis to identify recurring patterns related to EFL teaching methods, Islamic pedagogy, and learner motivation.The findings reveal that integrating Islamic values into EFL instruction enhances students’ motivation, engagement, and sense of identity. Islamic pedagogical principles, such as wisdom-based teaching, ethical dialogue, and storytelling, are found to align with modern EFL approaches like Communicative Language Teaching (CLT) and Task-Based Language Teaching (TBLT). Furthermore, the use of Islamic content, including Qur’anic narratives and moral themes, provides meaningful and contextually relevant learning experiences. Keywords : EFL; Teaching Method; Islamic Perspective